The hunger games - Collins, Suzanne (New York : Scholastic Press, 2011)
In a future North America, the rulers maintain control through an annual televised survival competition pitting young people from each of the twelve districts against one another, sixteen-year-old Katniss's skills are put to the test when she voluntarily takes her younger sister's place.
Keywords: Survival -- Fiction; Fantasy fiction